Quarantine And Antidotal e - Epidemiological Model For Viruses In Computer Network - Kumari, Kaveri Kanchan (Journal of Global Research in Mathematical Archives(JGRMA), 2018)
An e-epidemicÂ SIQRAS (Susceptible, Infectious, Quarantined, Recovered, Antidotal, Susceptible) model for the transmission of malicious objects in computer network has been developed and its various parametric characteristics are analyzed. Malicious objects, free equilibrium point and endemic equilibrium points are discussed by Jacobian Matrix. Stability of the system has been shown by using Routh-Hurwitz. MATLAB are employed to solve and simulate the system of differential equations.